Seni Patung dalam Tinjauan Agama Islam dan Hindu - Syahidatullah, Anisa; Novitasari, Shovi; Rosyidah; azzahro, Rufaidah (Sanaamul Quran: Jurnal Wawasan Keislaman, 2024)
This paper discusses Islamic and Hindu views on sculpture, particularly in the context of history, law, and social practice in Indonesia. In Islam, there are diverse views among scholars regarding the law of sculpture, with many forbidding it, especially when it resembles a living being, because it is feared that it will lead to idolatry. Meanwhile, in Hinduism, statues have an important role as a medium of worship and spiritual symbols, serving to connect the worshipper with the Divine. This research uses a qualitative method through literature review to explore the views of both religions towards statues and illustrate how these differences affect Indonesian society in religious practice. This study is expected to provide insight into the role of sculpture in maintaining religious and cultural values in society.